Software system for early diagnosis of strokes «Strokeml» - Іваненко, В. Ю. (ХНУРЕ, 2021)
The aim of the work is to develop a software system that allows the user to be tested, analyzes its results and provides the user with information about his susceptibility to stroke disease. The software system also aims to preserve the results of tests and provide recommendations for nutrition and healthy living.
Scientific supervisor of work – Iryna Leshchynska Candidate of Technical Sciences, Associate Professor of the Department of Software Engineering
Keywords: software system; diagnosis of strokes «Strokeml»